Cross-Modal Interactions of the Tactile System. (October 2022) - Sathian, K.; Lacey, Simon
The sensory systems responsible for touch, vision, and hearing have traditionally been regarded as mostly separate. Contrary to this dogma, recent work has shown that interactions between the senses are robust and abundant. Touch and vision are both commonly used to obtain information about a number of object properties, and they share perceptual and neural representations in many domains. Additionally, visuotactile interactions are implicated in the sense of body ownership, as revealed by powerful illusions that can be evoked by manipulating these interactions. Touch and hearing both rely in part on temporal-frequency information, which leads to a number of audiotactile interactions reflecting a good deal of perceptual and neural overlap. The focus in sensory neuroscience and psychophysics is now on characterizing the multisensory interactions that lead to humans' panoply of perceptual experiences.